Spiritualised political theology in a polarised political environment: A Pentecostal movement"s response to party politics in Zimbabwe - Musoni, Phillip (HTS teologiese studies, 2021)
This article interrogates the interface between the older Pentecostal movement and politics in Zimbabwe. The country continues to face political violence and a breakdown in rule of law. The Zimbabwean populace is asking whether the Zimbabwean Pentecostal movement is ready and able to exercise its prophetic role in promoting real peace and democracy. Many Zimbabweans are asking this question, because the track record shows that whilst most mainline churches have been consistent in becoming the voice of the voiceless, some Zimbabwean Pentecostal churches seem to have been sitting on the fence for too long by adopting a middle of the road stance, thereby avoiding a head-on confrontation with the corrupt Zimbabwe African National Union–Patriotic Front (ZANU–PF) government. In this article, I argue that for many decades the Zimbabwean Pentecostal movement has taken what one might refer to ironically as a ‘smart approach to politics’–in which the image of the ZANU–PF government is sanitised by espousing what I call a ‘spiritualised political theology.’ I use this critique, whilst remaining cognisant of the fact that the primary motivation of the movement on which I focus in this article, was evangelism, not politics. Thus, for the purpose of this research, the Zimbabwe Assemblies of God Africa (ZAOGA) of Apostle Ezekiel Guti was sampled to investigate its prophetic voice in a polarised political environment. This article examines the history of Apostle Guti’s political subterfuge based on the reflections of his pastoral letters referred to as the ‘Ten-days prayer letters’ issued since 1975 up to the time of writing this article. It is important at this early stage to outline that these letters were not political statements or meant to address politics only but theological letters addressing different social ills including politics. Thus, reading this letter one shall see that Apostle’s political subterfuge demonstrated a continuous oscillation of a theological position on how the church should relate to politics. Furthermore, I undertake a brief examination of other few millennial Zimbabwean Pentecostal churches to see if this political subterfuge transcended elsewhere thereby propagating a spiritualised political theology.Contribution: What is key to note is the fact that the Zimbabwean Pentecostal movement remained insignificant with regard to democratization agenda even after the removal of President Mugabe. The above claim is evidenced by the Zimbabwean Pentecostal church founders’ continuous political subterfuge authenticated by a propagation of a spiritualized political theology.